2020
DOI: 10.1371/journal.pone.0237297
|View full text |Cite|
|
Sign up to set email alerts
|

Gender differences in predictors of intensive care units admission among COVID-19 patients: The results of the SARS-RAS study of the Italian Society of Hypertension

Abstract: Background The global rate of intensive care unit (ICU) admission during the COVID-19 pandemic varies within countries and is among the main challenges for health care systems worldwide. Conflicting results have been reported about the response to coronavirus infection and COVID-19 outcomes in men and women. Understanding predictors of intensive care unit admission might be of help for future planning and management of the disease. Methods and findings We designed a cross-sectional observational multicenter na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
155
2
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(205 citation statements)
references
References 31 publications
21
155
2
9
Order By: Relevance
“…In contrast, two other studies that respectively enrolled 416 and 1591 patients suggested that after the adjustment for confounders, hypertension was no longer an independent risk factor for COVID-19 [19,20].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In contrast, two other studies that respectively enrolled 416 and 1591 patients suggested that after the adjustment for confounders, hypertension was no longer an independent risk factor for COVID-19 [19,20].…”
Section: Discussionmentioning
confidence: 78%
“…The previous studies about other pneumonia demonstrated that preexisting hypertension could not independently contribute to disease progression [15,16]. Concurrently, multiple studies on COVID-19 evaluating whether the history of hypertension is a risk factor for adverse outcomes have yielded conflicting results [17][18][19][20][21][22]. Specifically, Pan et al found that hypertension has an HR of 1.80 for in-hospital mortality in 996 patients with COVID-19 [17], and Gao et al…”
Section: Discussionmentioning
confidence: 99%
“…A review of the symptom burden of COVID‐19 highlighted that dyspnoea is the most prominent symptom, but the primary cause of death is by respiratory failure or HF or both 25 . In a large observational study, nearly three‐quarters of patients diagnosed with COVID‐19 had at least one pre‐existing condition, and over half were hypertensive 26 . In end‐stage HF patients, myocardial injury has resulted from COVID‐19, 27 but the pathophysiological mechanisms between the virus, cardiac injury, and HF are not yet understood 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Elderly patients are less possibly to survive from a severe infection, MOF, heart and lung failure, as well as inflammatory storms leading to malignant arrhythmia, nutritional deficiencies, and electrolyte, and acid–base imbalances. Also, comorbidities greatly increase by age, including hypertension, chronic kidney disease, diabetes mellitus, chronic obstructive pulmonary disease, and thrombotic disease, which also contribute to poor survival rates in elder COVID‐19 patients 21,22 . The characteristics of severe and critical COVID‐19 patients were significantly different from the mild and moderate degree cases, which is much more sensitive to myocardial injury‐causing heart failure and deaths.…”
Section: Discussionmentioning
confidence: 99%